TINGKAT MARGIN DAN KEMUDAHAN AKSES TERHADAP KEPUTUSAN NASABAH DALAM MENGAMBIL PEMBIAYAAN MURABAHAH: STUDI KASUS PADA BMT AN NAAFI, BOYOLALI - Hendra Ikhsan Suryanto; Amri Syarif Hidayat (ITB AAS Indonesia Surakarta, 2025)
Murabahah financing is a leading product offered by Islamic microfinance institutions such as BMT An-Naafi. The margin rate, a key component in calculating financing costs, is a significant concern for customers. This study examines the effects of the margin rate and ease of access on customer decisions regarding murabahah financing at BMT An-Naafi. Employing a quantitative approach with multiple linear regression, the study's population comprises all BMT An-Naafi customers, with a sample of 65 customers who have utilized murabahah financing. The results indicate that competitive margin rates are a primary factor attracting customer interest. While ease of access did not show a statistically significant effect in this study, improvements through digital innovation or procedural simplification are recommended to enhance the overall attractiveness of murabahah financing.